2022
DOI: 10.1038/s41598-022-13620-4
|View full text |Cite
|
Sign up to set email alerts
|

Jaw1/LRMP increases Ca2+ influx upon GPCR stimulation with heterogeneous effect on the activity of each ITPR subtype

Abstract: Ca2+ influx upon G protein-coupled receptor (GPCR) stimulation is observed as a cytosolic Ca2+ concentration oscillation crucial to initiating downstream responses including cell proliferation, differentiation, and cell–cell communication. Although Jaw1 is known to interact with inositol 1,4,5-triphosphate receptor (ITPRs), Ca2+ channels on the endoplasmic reticulum, the function of Jaw1 in the Ca2+ dynamics with physiological stimulation remains unclear. In this study, using inducible Jaw1-expressing HEK293 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…S3). Jaw1 has an additional role to increase the Ca 2+ release from the ER via interaction with IP 3 Rs upon GPCR stimulation, as we recently reported (Okumura et al ., 2022). Therefore, we measured Ca 2+ flux in Jaw1 KO Flp-In T-REx HEK293 (Jaw1 KO), Jaw1 IE, and AASS IE cells via stimulation with ATP.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…S3). Jaw1 has an additional role to increase the Ca 2+ release from the ER via interaction with IP 3 Rs upon GPCR stimulation, as we recently reported (Okumura et al ., 2022). Therefore, we measured Ca 2+ flux in Jaw1 KO Flp-In T-REx HEK293 (Jaw1 KO), Jaw1 IE, and AASS IE cells via stimulation with ATP.…”
Section: Resultssupporting
confidence: 57%
“…We previously reported that Jaw1 interacts with IP 3 Rs via its coiled-coil domain, and a mutant lacking the coiled-coil domain, has no augmentative effect of Jaw1 on the Ca 2+ signaling, which indicates that Jaw1 directly increases the Ca 2+ release activity of IP 3 Rs (Okumura et al ., 2022). In this study, the augmentative effect of the AASS mutation on the Ca 2+ release from the ER was slightly lower than that of wild-type Jaw1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations